REFORMASI PROTESTAN DAN PERANG AGAMA PERANCIS - Nugroho Nugroho (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2019)
Protestant Reformation emerged in the 16th century in Europe caused economic factors, politics, nationalism, individualism, renaissance, as well as the practice of indulgences. This study is library research and analyzed with descriptive analytic. Protestant Reformation led to divisions and wars in Christianity that is so terrible that resulted in the sacrifice of life. Resolutions taken the result of the reform protestanya The Peace of Westphalia.